Ocular Problems among Video Display Terminal Users in a Software Company of Sector V, Kolkata - Basu, Rivu; Dasgupta, Aparajita (Indian Journal of Community Health, 2020)
Background: Video Display Unit use and Information Technology creates a host of problems like Ocular Problems and Work Related Musculo Skeletal Problems. Many experience visual symptoms including eyestrain, headaches, ocular discomfort, dry eye, diplopia and blurred vision either at near or when looking into the distance after prolonged computer use. Very few and sporadic studies have been done in this part of the world especially in India, to address the issue in all its scope. Aim & Objective: To find out the proportion of different ocular problems among the study population and to find out the association of their ocular problems with the socio-demographic, work related and ergonomic factors. Materials and methods: It was an institution based, cross sectional, analytical epidemiological study and was conducted over one-year period. The study population comprised of persons working with Video Display Terminals. A predesigned, semi-structured instrument for elaborating the socio-economic, lifestyle related and a few job-related health behaviors were used. Combination of few instruments to elicit different morbidities like and many ergonomic checklists to evaluate office workspace were also used. Results: Of the total 79.1 % had any kind of ocular problems currently, with around 65% of them reporting to be having problem constantly in the last 12 months. Headache (63.6%) seemed to be the most important problem, followed by Eye fatigue (52.4%). Repetition of work and poor ergonomic practices turned out to be the statistically significant factors. Increased Years of working and female sex were also found to be important factors. Screen Character was found to be the most important risk factor of eye problems. Conclusion: A simple model was proposed where interaction of Individual factors and factors related to workstation was identified as the main culprit, which exaggerated by the repetition of work.